CTNI-29. CODEL: PHASE III TRIAL OF RT ALONE, RT PLUS TMZ, OR TMZ ALONE FOR NEWLY-DIAGNOSED, 1p/19q CODELETED ANAPLASTIC OLIGODENDROGLIOMA. ANALYSIS FROM THE INITIAL STUDY DESIGN. (NCCTG N0577, ALLIANCE). (9th November 2020) - Jaeckle, Kurt; Ballman, Karla; van den Bent, Martin; Giannini, Caterina; Galanis, Evanthia; Brown, Paul; Jenkins, Robert; Cairncross, Gregory; Wick, Wolfgang; Weller, Michael; Aldape, Kenneth; Dixon, Jesse; et al.
Abstract: BACKGROUND: The original 3-arm CODEL design included a radiotherapy (RT)-alone control arm, an RT plus temozolomide (TMZ) arm, and an exploratory TMZ-alone arm. We report the analysis involving patients treated per the initial design. METHODS: Adults (18+ years) with newly-diagnosed 1p/19q codeleted WHO grade III oligodendroglioma were randomized to RT (5940 cGy) alone (Arm A); RT with concomitant and adjuvant TMZ (Arm B); or TMZ alone (Arm C). Primary endpoint was OS, Arm A vs. B. Secondary comparisons were performed for OS and PFS, comparing pooled RT arms with the TMZ-alone arm. RESULTS: 36 patients were randomized equally to the three arms. At median follow-up of 7.5 years, 83.3% (10/12) TMZ-alone patients had progressed, versus 37.5% (9/24) patients on the RT arms. PFS was shorter in TMZ-alone patients compared to RT-treated patients (HR=3.12; 95% CI: 1.26, 7.69; p=0.014). Death from disease progression occurred in 3/12 (25%) of TMZ-alone patients and 4/24 (16.7%) of RT-treated patients. OS did not statistically differ between arms, although this comparison was underpowered. After adjustment for IDH status (mutated vs. wildtype) in a Cox regression model, with IDH status and RT treatment status as co-variables (Arm C vs pooled A and B), PFS remained shorter for patients not receiving RT (HR= 3.33; 95% CI: 1.31, 8.45; p=0.011), and OS differences remained non-significant ((HR = 2.78; 95% CI 0.58, 13.22, p=0.20). Grade 3+ adverse events occurred in 25%, 42% and 33% patients (Arms A, B and C, respectively). Neurocognitive assessments, comparing baseline and 3 month timepoints, showed no significant differences between arms. CONCLUSIONS: TMZ-alone treated patients experienced significantly shorter PFS than patients treated on the pooled RT arms, which remained significant when adjusting for IDH status. CODEL has been redesigned to compare the efficacy and toxicity of RT+PCV versus RT+TMZ. Clinicaltrials.gov Identifier: NCT00887146. Support: U10CA180821, U10CA180882, https://acknowledgments.alliancefound.org .